2006
DOI: 10.1063/1.2400513
|View full text |Cite
|
Sign up to set email alerts
|

Negative Barkhausen jumps in permalloy thin-film microstructures

Abstract: Dual-beam high-resolution magneto-optic Kerr effect polarimetry and magnetic force microscopy ͑MFM͒ are used to study Barkhausen jumps in thin-film permalloy microstructures. Negative jumps ͑changes in local magnetization that oppose the drive field͒ are always accompanied by a nearly simultaneous positive jump, and the power-law dependence of jump-size statistical distributions of positive and negative jumps are similar. These observations, supported by sequential MFM domain images taken during field-driven r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The calculated ΔH B nicely fit with the experimental data. 9) These numerical simulations in §3 clearly show the general magnetization characteristics such as the magnetization curves, the B effects and the ΔH B distributions, which also coincide with the experimental data in good agreements. 9)-13)…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…The calculated ΔH B nicely fit with the experimental data. 9) These numerical simulations in §3 clearly show the general magnetization characteristics such as the magnetization curves, the B effects and the ΔH B distributions, which also coincide with the experimental data in good agreements. 9)-13)…”
Section: Introductionsupporting
confidence: 70%
“…The observation of negative Barkhausen jumps is reported in ref. 9) with permalloy thin-film microstructures as a violent case.…”
Section: Long Nano-belt System and Domain Break Down Avalanchesmentioning
confidence: 99%
“…structures. [42][43][44] Each vortex DW is characterized by two integers p the polarization and q the vorticity. p = Ϯ 1 indicates whether n in the vortex core is pointing upward or downward and q = Ϯ 1 is the winding number of n around the vortex core.…”
Section: S N(xt)mentioning
confidence: 99%
“…Monte Carlo simulations have shown that the negative susceptibility around zero field is indeed associated to dislocations because of spin fluctuations [3]. Finally, negative Barkhausen jumps may be possible if the increase in the local Zeeman energy is associated with a local magnetic configuration with the magnetization opposing the applied field [11]. Concluding, the vector Preisach model proposed is promising for use with magnetic NDT techniques while the role of the differential permeability in magnetic NDT needs to be further investigated.…”
Section: Resultsmentioning
confidence: 95%